Epicure: a European epidemiological study of patients with an advanced or metastatic Urothelial Carcinoma (UC) having progressed to a platinum-based chemotherapy. Issue 1 (December 2016) - Houédé, N.; Locker, G.; Lucas, C.; Parra, H.; Basso, U.; Spaeth, D.; Tambaro, R.; Basterretxea, L.; Morelli, F.; Theodore, C.; Lusuardi, L.; Lainez, N.; et al.
Abstract Background Platinum-based systemic chemotherapy is considered the backbone for management of advanced urothelial carcinomas. However there is a lack of real world data on the use of such chemotherapy regimens, on patient profiles and on management after treatment failure. Methods Fifty-one randomly selected physicians from 4 European countries registered 218 consecutive patients in progression or relapse following a first platinum-based chemotherapy. Patient characteristics, tumor history and treatment regimens, as well as the considerations of physicians on the management of urothelial carcinoma were recorded. Results A systemic platinum-based regimen had been administered as the initial chemotherapy in 216 patients: 15 in the neoadjuvant setting, 61 in adjuvant therapy conditions, 137 in first-line advanced setting and 3 in other conditions. Of these patients, 76 (35 %) were initially considered as cisplatin-unfit, mainly because of renal impairment (52 patients). After platinum failure, renal impairment was observed in 44 % of patients, ECOG Performance Status ≥ 2 in 17 %, hemoglobinemia < 10 g/dL in 16 %, hepatic metastases in 13 %. 80 % of these patients received further anticancer therapy. Immediately after failure of adjuvant/neoadjuvant chemotherapy, most subsequent anticancer treatments were chemotherapy doublets (35/58), whereas after therapy failure in the advanced setting most patients receiving further anticancer drugs were treated with a single agent (80/114). After first progression to chemotherapy, treatment decisions were mainly driven by Performance Status and prior response to chemotherapy (>30 % patients). The most frequent all-settings second anticancer therapy regimen was vinflunine (70 % of single-agent and 42 % of all subsequent treatments), the main reasons evoked by physicians (>1 out of 4) being survival benefit, safety and phase III evidence. Conclusion In this daily practice experience, a majority of patients with urothelial carcinoma previously treated with a platinum-based therapy received a second chemotherapy regimen, most often a single agent after an initial chemotherapy in the advanced setting and preferably a cytotoxic combination after a neoadjuvant or adjuvant chemotherapy. Performance Status and prior response to chemotherapy were the main drivers of further treatment decisions.